The statutes at large; being a collection of all the laws of Virginia, from the first session of the Legislature in the year 1619. By William Waller Hening. New York, Printed for the editor, 1819-23. - Hening, William Waller, 1768-1828 ([Published for the Jamestown Foundation of the Commonwealth of Virginia by the University Press of Virginia], 1969)
"Published pursuant to an act of the General Assembly of Virginia, passed on the fifth day of February one thousand eight hundred and eight."